Professional Identities in the NHS: Existential Perspectives (Existential Analysis: Journal of the Society for Existential Analysis, 1998)
This paper attempts to consider the experience of working in a manner strongly influenced by the existential-phenomenological paradigm. It does so by describing a particular setting, by presenting three personal accounts of working in this area and finally exploring the relationship between the setting, values and practices of the three authors.